Penggunaan Teknik Boundary Value Analysis untuk Pengujian Aplikasi Stok Barang - Tsalatsah, Ibnu Elna; Pratama, Dayu; Hakim, Arip Rahman; Budiman, Luqman Aziz; Riyanto, Joko (Program Studi Teknik Informatika Universitas Pamulang, 2022)
The application of data collection of goods in a store has many uses in running a sales business. By using a data collection application, errors will be minimized and management is better and controlled. In recording goods, business owners can monitor what items are needed when the availability of goods is running low. To minimize errors that occur testing the application is very necessary. This application will be tested in a GUI to check whether the GUI in the application has an error that causes the application to crash. For example, the price on the goods is listed with other characters that are difficult to remove, then before the test occurs, it must be done. Of the several testing methods, Black Box testing is the most commonly used. By using the Boundary Value Analysis method that is suitable for the application of the availability of goods. The method tests the maximum and minimum digits to produce valid values and is easy enough to test an application. The result of the analysis of the method used is the quality of the application that is in accordance with the function, and can be used properly by the user.